Serotype Infectivity and Phylogenetic of Dengue Virus cause of Dengue Fever (DF), Dengue Hemorrhagic Fever (DHF), and Dengue Shock Syndrome (DSS) in Surabaya- Indonesia - rantam, fedik (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
Infection with DENV causes a spectrum of clinical disease ranging. The aim of this study is to investigate the infectivity of DENV with degree of severity dengue infection in Surabaya. Dengue infection was established by IgM anti dengue, and two step multiplex RT PCR and Nucleotide sequence. Grading of degree severity infection follow the WHO criteria 2011. DSS cases found 3 from 36 patients caused by DENV 2. The most uninfective was DENV 1, and the most prevalence dengue infection caused by DENV 3. The infectivity of dengue infection shown 16 patients lead to severity with plasma leakage. All of sera patients detecting using multiplex RT-PCR were positive, but it were analyzed using Duo ELISA only 22 serum sera positive IgM and IgG from 36 sera. . The Phylogenetic analysis indicates that the isolates from 2011 to 2012 close related with dengue isolate from 1998 and belong to 2009 to 2020.In this study it indicates that DENV 2 predominantly is the cause of DSS.